COMPARATIVE REGULATION OF “INADMISSIBLE DECISIONS” IN CRIMINAL PROCEDURE LAW BETWEEN INDONESIA AND GERMANY - Bayu Akbar Wicaksono; Milda Istiqomah; Rika Kurniaty (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
This article examines the comparative regulation of “inadmissible decisions” in criminal procedure law between Indonesia and Germany. Comparative law is used as an analytical approach to identify similarities and differences between the two legal systems, aiming to formulate clearer and more systematic procedural norms. Both countries belong to the civil law tradition, which emphasizes codification and legal certainty. Germany recognizes two key mechanisms related to inadmissible decisions, namely Verfahrenshindernis (procedural obstacles) and Unzulässige Anklage (inadmissible indictment). These mechanisms serve as legal filters to ensure procedural compliance and the protection of defendants’ rights before the main trial begins. This study concludes that Germany’s systematic procedural framework offers a valuable model for reformulating the normative and procedural basis of inadmissible decisions in Indonesia.